PTU-117 Chest xray interpretation of nasogastric tube placement by medical registrars: how safe is it?. (17th June 2017) - Tierney, M; Sibley, C; Leach, Z; Rutter, C; Pither, C; Smith, T
Abstract : Introduction: Nasogastric (NG) tube feeding is an important component of nutritional care. However it has risks and introducing feed or medicines into the respiratory tract through a misplaced NG tube is categorised as a 'never event' by NHS England. If confirmation of safe NG tube placement requires a chest x-ray (CXR), this must be interpreted by competent staff. This study aimed to establish whether documentation of CXRs by medical registrars was safe and compliant with National Patient Safety Agency guidance. Method: A group of medical registrars (ST3 to ST7 and from various specialties) in the Wessex region were presented with a CXR and asked to document a correctly sited NG tube. The four criteria to confirm NG position are: Does the tube follow the contours of the oesophagus and avoid those of the bronchi? Does the tube clearly bisect the carina or bronchi? Does it cross the diaphragm in the midline? Is the tip clearly visible below the left hemi-diaphragm? Results: 34 responses were obtained. Results were categorised depending on whether they met one to four of the criteria. All four were met in 17.6%, three were met in 29.4%, two were met in 8.8% and one criterion was met in 23.5%. Responses were considered incorrect in 20.5%. 38.2% commented that it was safe to use the tube. 61.7% recorded whether the NG should be used or not. Conclusion: Documentation by a group of senior medical trainees of NG tube position met the NPSA recommendations in only 17.6% of responses. 82.4% of responses were inadequate and therefore unsafe. This raises significant concerns about competence in assessing NG tube position by these trainees. A pathway and rolling education programme needs to be developed to support the safe reporting of CXRs, where safe NGT placement needs to be confirmed. Reference: . National Patient Safety Agency Alert 2011/PSA/02 Reducing the harm caused by misplaced nasogastric feeding tubes in adults, children and infants 2011http://www.nrls.npsa.nhs.uk/resources/type/alerts/?entryid45=129640 Checking placement of nasogastric feeding tubes in adults (interpretation of x ray images): summary of a safety report from the National Patient Safety Agency BMJ 2011;342:d2586 Disclosure of Interest: None Declared